Immunomodulation by mucosal gene transfer using TGF-beta DNA. - Kuklin, N A (1998)
This report evaluates the efficacy of DNA encoding TGF-beta administered mucosally to suppress immunity and modulate the immunoinflammatory response to herpes simplex virus (HSV) infection. A single intranasal administration of an eukaryotic expression vector encoding TGF-beta1 led to expression in the lung and lymphoid tissue. T cell-mediated immune responses to HSV infection were suppressed with this effect persisting as measured by the delayed-type hypersensitivity reaction for at least 7 wk. Treated animals were more susceptible to systemic infection with HSV. Multiple prophylactic mucosal administrations of TGF-beta DNA also suppressed the severity of ocular lesions caused by HSV infection, although no effects on this immunoinflammatory response were evident after therapeutic treatment with TGF-beta DNA. Our results demonstrate that the direct mucosal gene transfer of immunomodulatory cytokines provides a convenient means of modulating immunity and influencing the expression of inflammatory disorders.